A Qur’anic framework for spiritual intelligence - Bensaid, Benaouda; Machouche, Salah; Grine, Fadila (Multidisciplinary Digital Publishing Institute, 2014)
This paper examines the perspective of the Qur’an on spiritual intelligence in an attempt to understand its meaning and nature, foundations, and derive its indicators, in an effort to develop a competency-based criterion for it. This paper draws on some illustrations that effectively highlight the Qur’anic perspective on the subject of spiritual intelligence. The paper concludes that spiritual intelligence developed in accordance with a Qur’anic framework that incorporates spiritual consciousness into a system of belief, worship, morality and social responsibility. The understanding of the Qur’anic perspective helps uncover some of the broad underlying theoretical principles and values of Islamic spiritual intelligence which shapes much of Muslim spiritual undertaking with relation to a wider spectrum of interaction with faith-groups and society; effectively developing more inclusive models of evaluation and capacity-building in contemporary multi-religious societies.